Мова для людини чи людина для мови? - Хомич, Т. Л. (Видавництво НДУ ім.М. В. Гоголя, 2017)
Пропоновану статтю присвячено проблемі окреслення причин побутування російської мови на землях української Чернігівщини та можливостей змінити мовленнєву ситуацію регіону. Зʼясовано такі причини сучасної мовленнєвої ситуації: провінційність населення міста Чернігова; наявність комплексу меншовартості, неповноцін-ності; багаторічна цілеспрямована загальноохоплювальна гено-цидна політика.
Ukrainian modernity sharply permeates the linguistic question: what language should communicate Ukrainian, what language to get education, what language can be heard from TV and radio, etc. The language problem is the subject of discussions in the socio-cultural and political sectors, and it has been stated about it in a number of sociolinguistic studies of Ukrainian scholar: N. Babich, M. Ginzburg, K. Gorodenska, P. Grytsenko, V.Greshchuk, S. Yermolenko, E. Karpilovskaya, J. Koloiz, L. Masenko, L. Matsko, V. Rusnovsky, P. Seligia, O. Serbenskaya, M. Stepanenko, O. Tkachenko, I. Farion, I. Khomyaka, I. Yuschuk and many others. The article focuses on the problem of defining the reasons of the Russian language existence on the lands of Ukrainian Chernihiv region and the possibilities to change the speech situation in the region. Іntelligence raises the problem of those who are hardest today – people who speak the Ukrainian language, surrounded by the so-called Russian. The following reasons for the current speech situation are explained. The population of Chernihiv is predominantly provincial, its inhabitants are from rural areas, for which dialectal speech is typical. To reach a certain standard of living, the person tends not to "stand out", "to be his own", "to merge with the masses". Of course, such a person will not speak his dialect, but will try to master the common sense. Another reason why a Ukrainian-speaking person goes to Russian is a complex of the inferiority of society. If the spokesman does not feel completely self-sufficient in his everyday life (and this is for the modern society to be an objective norm), he again begins to adapt to the circumstances. Russian colloquial in Chernihiv is the result of a targeted generalized genocidal policy. It is a "norm" for everyone who has fallen into the thorn of the Soviet Union. It is possible to clear this from the consciousness of Ukrainians only with the condition of similar scientifically grounded political state activity.
Keywords: українська мова; рідна мова; російська мова; мовець